2010
DOI: 10.1039/c000337a
|View full text |Cite
|
Sign up to set email alerts
|

Size control and compartmentalization in self-assembled nano-structures of a multisegment amphiphile

Abstract: A ''multisegment amphiphile'' has been synthesized by covalently connecting two well known building blocks, a gelator and a micelle forming surfactant. Self-assembly results in the formation of compartmentalized nano-object displaying properties inherited from both parents.Amphiphiles continue to attract widespread attention in science and technology, not only because of their fascinating self-assembly properties, but also because their numerous, diverse applications in e.g. detergent formulations, catalysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…51, 52 Solutions of molecules 1 and 2 , ranging from 1 μM to 1000 μM in PBS, were prepared from stock solutions, and Nile Red in ethanol was diluted 200-fold into solutions to a final concentration of 250 nM. Using a NanoLogHJ spectrofluorometer, the samples were excited at 550 nm and the spectra were collected from 580 – 750 nm.…”
Section: Methodsmentioning
confidence: 99%
“…51, 52 Solutions of molecules 1 and 2 , ranging from 1 μM to 1000 μM in PBS, were prepared from stock solutions, and Nile Red in ethanol was diluted 200-fold into solutions to a final concentration of 250 nM. Using a NanoLogHJ spectrofluorometer, the samples were excited at 550 nm and the spectra were collected from 580 – 750 nm.…”
Section: Methodsmentioning
confidence: 99%
“…As a model system, we use a previously described multisegment amphiphile that consists of two covalently linked but orthogonally self-assembling building blocks, and which forms architectures characterized by each individual segment. [9] Through the addition of a chaperone analogue we can selectively switch off the self-assembly of each of these segments individually, resulting in architectures of the other segment. Interestingly, not only the morphologies of the other segment are retained, but also its dynamics of self-assembly.…”
mentioning
confidence: 99%
“…[11a] We have previously shown that MA 3 in water assembles into architectures that display properties of both parental segments. [9] The gelator segment forces these molecules to stack into fibrils because of intermolecular hydrogen bonding and these fibrils assemble into tapes caused by the hydrophobic interactions between the surfactant segments (Figure 1 b). These tapes form an entangled network in the solvent leading to turbid gels above a critical gelation concentration (cgc) of 5.0 mm.…”
mentioning
confidence: 99%
“…The multisegment amphiphile (MA 3 ) is constructed of a gelator10 segment reminiscent of gelator 1 and a surfactant segment reminiscent of EO 4 C 8 (surfactant 2 ), which assemble orthogonally (Figure 1 a). 11a We have previously shown that MA 3 in water assembles into architectures that display properties of both parental segments 9. The gelator segment forces these molecules to stack into fibrils because of intermolecular hydrogen bonding and these fibrils assemble into tapes caused by the hydrophobic interactions between the surfactant segments (Figure 1 b).…”
mentioning
confidence: 96%
“…Herein we demonstrate that morphological transitions can easily be programmed by separately addressing the complex aggregation behavior of a segmented self‐assembling molecule, using small molecule chaperone analogues, that is, small molecules that selectively switch off self‐assembly of another molecule through selective association. As a model system, we use a previously described multisegment amphiphile that consists of two covalently linked but orthogonally self‐assembling building blocks, and which forms architectures characterized by each individual segment 9. Through the addition of a chaperone analogue we can selectively switch off the self‐assembly of each of these segments individually, resulting in architectures of the other segment.…”
mentioning
confidence: 99%